2019
DOI: 10.1111/jopr.13058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bonding Agent on Metal‐Ceramic Bond Strength between Co‐Cr Fabricated with Selective Laser Melting and Dental Feldspathic Porcelain

Abstract: Purpose:To investigate the effect of bonding agent on the bonding strength between Co-Cr dental alloy, prepared by selective laser melting (SLM), and feldspathic porcelain. Materials and Methods:The experiments were conducted according to ISO 9693 and the conventional protocols for the production of metal-ceramic dental restorations. After Al 2 O 3 air-particle abrasion, metal substrates of Co-Cr dental alloy specimens were bonded, using bonding agent (25 specimens), with dental porcelain positioned in layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 27 publications
0
34
0
6
Order By: Relevance
“…This supports the suggestion of the manufacturers that metal bonding agents affect bond strength by reducing the thickness of the oxide layer and compensating for differences in coefficient of temperature expansion between ceramic and Co-Cr alloy. A previous study reported that use of a metal bonding agent increased the Weibull modulus [ 37 ]. This means that the presence of bonding agent narrowed the scatter of values of bond strength; in other words, a more reliable interface between ceramic and metal was produced.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the suggestion of the manufacturers that metal bonding agents affect bond strength by reducing the thickness of the oxide layer and compensating for differences in coefficient of temperature expansion between ceramic and Co-Cr alloy. A previous study reported that use of a metal bonding agent increased the Weibull modulus [ 37 ]. This means that the presence of bonding agent narrowed the scatter of values of bond strength; in other words, a more reliable interface between ceramic and metal was produced.…”
Section: Discussionmentioning
confidence: 99%
“…The results of three‐point bending strength tests (Autograph AGS‐H; Shimadzu), carried out with a crosshead speed of 1.0 mm/min and a span of 25 mm between the supporting rods, allowed the calculation of the flexural strength ( σ ) and the modulus of elasticity ( E ) by using the following Equations () and (3), 2,12 respectively:σ=3FL2wh2,andE=L3m4wh3,where, F is the load at fracture load, and L , w , and h are the span between the supporting rods, and the specimen width and thickness (25, 4, and 3 mm), respectively. The slope of the load versus displacement is denoted with m. Ten specimens for each composition (i.e., n = 10, for each group) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanical bonding is related to compressive forces from the difference in the coefficients of thermal expansion of metal and ceramics 10 , or to the surface roughness and retentive edges in the metal structure, which may favor wettability 12 . Chemical bond occurs when the elements of dental alloys, such as cobalt, chromium, and molybdenum 13 , undergo surface oxidation forming ion channels, where the diffusion of atoms present in metal-ceramic interface occurs 13 . The composition and morphology of this oxide layer depends on the type of surface treatment performed 14 as well as interaction among atoms from both metal and ceramic 12 , which may interfere in MCBS [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Chemical bond occurs when the elements of dental alloys, such as cobalt, chromium, and molybdenum 13 , undergo surface oxidation forming ion channels, where the diffusion of atoms present in metal-ceramic interface occurs 13 . The composition and morphology of this oxide layer depends on the type of surface treatment performed 14 as well as interaction among atoms from both metal and ceramic 12 , which may interfere in MCBS [13][14][15] . If the thickness of this film reduces in the sintering process, the MCBS decreases 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation